A dynamic communication approach for data fusion in IEEE 802.15.4 wireless sensor networks - Gerson F. Budke (2012)
In this paper is proposed a novel communication approach for implementation of parallel data fusion techniques in Wireless Sensor Networks. The approach is carried out by a distributed algorithm implemented in each network sensor node. In this approach, the network configures itself in order to adjust the number of messages sent periodically, establishing a tradeoff between the number of sent messages and the quality of data fusion (QoF). A prototype was implemented and experimental results show the effectiveness of this proposal.